Adverse impact of elevated serum progesterone and luteinizing hormone levels on the hCG trigger day on clinical pregnancy outcomes of modified natural frozen-thawed embryo transfer cycles - Huang, Chenyang; Shen, Xiaoyue; Shi, Qingqing; Shan, Huizhi; Yan, Yuan; Liu, Jingyu; Kong, Na (Frontiers in Endocrinology, 2022)
Research question: The relationship between serum progesterone (P) and luteinizing hormone (LH) levels on the human chorionic gonadotropin (hCG) trigger day and the clinical pregnancy outcomes in modified natural frozen-thawed embryo transfer (mNC-FET) cycles are controversial. Design: This was a retrospective study of 788 mNC-FET cycles. A smooth fitting curve and threshold effect analysis was performed to identify the effect of serum P and LH levels measured on the hCG day on the clinical pregnancy rate (CPR) and live birth rate (LBR) of mNC-FET cycles. Results: The CPR and LBR decreased significantly when the LH level on the hCG day was greater than or equal to 32 IU/L. Further subgroup analysis showed that the CPR decreased significantly when the P level on the hCG day was equal to or greater than 1 ng/mL. When the P level was lower (< 1 ng/mL), the patients with an LH level greater than or equal to 32 IU/L had reduced CPR and LBR in mNC-FET cycles. Conclusion: Applying the hCG trigger on a day with a higher P level (≥ 1 ng/mL) leads to a decreased CPR and LBR. hCG administration with a higher LH level (≥ 32 IU/L) also leads to a decreased CPR and LBR in mNC-FET cycles when the P level is less than 1 ng/mL.